Capital social e o nível desenvolvimento da educação básica no estado do Rio Grande do Sul - Borghetti, Júlio César (Universidade do Vale do Rio dos Sinos, 2013)
The performance of Brazilian education has been closely monitored by society, who intently to the question of quality, observes the performance indicators (National High School Exam, Index of Basic Education Development, National Survey of Student Performance) that justify the investments public and private area. In the literature identified potential factors that could affect the evaluation indicators of education, reaching the capital hypothesis. Thus, the goal of research is to analyze whether social capital has an impact on student performance on tests of Development Index of Basic Education. To this end, it was estimated by ordinary least squares regression model where the classical linear Development Index of Basic Education is the dependent variable and capital is the independent variable and interest. Data were collected in the Annual Social Information Foundation of Economics and Statistics, Institute of Geography and Statistics. As a result, it was observed that 15.16% of the variations Development Index of Basic Education are explained by capital and control variables. Moreover, the share capital was presented as dependent variable significant, thus confirming the goal post.
Keywords: Development of education; Social capital; Rio Grande do Sul; Capital social; Desenvolvimento da educação; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis